Quantifying the Extensive Margin(s) of Trade: The Case of Uneven European Integration - James E. Anderson; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2022)
We propose a short-run theory of the extensive margins of trade, comprising the standard international extensive margin and a novel domestic extensive margin. The domestic extensive margin allows identification of globalization and specific policy effects not properly identified in previous literature. To apply our methods, we build a new dataset covering both the cross-border and domestic extensive margins for 35 countries, 1995-2014. We deploy it to quantify the extensive margins effects of globalization and European integration. We find strong positive effects of globalization and also significant but highly asymmetric effects of European integration in favor of more developed EU members.
Keywords: F13; F14; F16; 330; extensive margin; domestic extensive margin; globalization; EU; gravity